Karakteristik Pendekatan Yuridis Terhadap Tindakan Integrasi Vertikal Dalam Struktur Pasar Duopoli - Akbar Rizky Pratama (Jurist-Diction, 2024)
AbstractIn this era of development, the need for online transportation as one of the options to move to the destination certainly attracts the attention of several companies that provide online transportation services. In Indonesia itself, this online transportation competition was initiated by three companies. But in its development, GO-JEK and Grab remain as two big competitors in the world of online transportation, which gives rise to a duopoly market structure that makes it difficult for other companies that want to enter the world of online transportation services to get customers. This article uses conceptual and statutory research to examine the conditions of the duopoly market and the company's responsibilities if there are violations. It was found that in relation to the conditions of the duopoly market, per se illegal, and rule of reason approach is needed to determine whether the action is prohibited or not. Furthermore, when viewed from a vertical integration approach, of course the two companies are allowed with the aim of saving and efficiency. However, if it is done to control the operation of online transportation services, of course it is categorized as unfair business competition.Keyword: Vertical Integration; Duopoly Market; Online Transportation; Per Se Illegal; Rule of Reason. AbstrakDengan adanya perkembangan jaman, tentu saja kebutuhan transportasi online sebagai salah satu pilihan untuk berpindah ke lokasi tujuan tentunya menarik perhatian beberapa perusahaan untuk menyajikan layanan transportasi Online. Di Indonesia sendiri, persaingan transportasi online ini diawali oleh tiga perusahaan. Dalam perkembangannya tersisa GO-JEK dan Grab sebagai dua pesaing berat di dunia transportasi online yang menimbulkan adanya struktur pasar duopoli sehingga timbul kesulitan perusahaan lain yang ingin terjun ke dalam dunia jasa transportasi online untuk mendapatkan pelanggan. Artikel ini menggunakan penelitian konseptual dan perundang-undangan untuk mengkaji kondisi pasar duopoli dan pertanggungjawabannya apabila terdapat pelanggaran. Ditemukan bahwa berkaitan dengan kondisi pasar duopoli, diperlukan adanya suatu pendekatan pendekatan per se illegal dan rule of reason untuk menentukan apakah tindakan tersebut dilarang atau tidak. Terlebih lanjut apabila dilihat dari pendekatan integrasi vertikal, tentunya kedua perusahaan tersebut diperbolehkan dengan tujuan untuk penghematan dan efisiensi. Akan tetapi, apabila dilakukan untuk menguasai operasi jasa transportasi online, tentunya dikategorikan sebagai persaingan usaha tidak sehat. Kata Kunci: Integrasi Vertikal; Pasar Duopoli; Transportasi Online; Per Se Illegal; Rule of Reason.